Pwerta - Hernaez, Aironne Danielle B. 1993-; Dalena, Sari Raissa L.; University of the Philippines. College of Mass Communication (2014)
"Pwerta tells the story about Isabelle who's been caged by her mother since she was born. The only person who can step in the vicinity of their home is Edgar, a mailman. Isabelle and Edgar have a secret relationship and by the time they are going to be intimate, Edgar discovered that Isabelle is a man. The character of Isabelle's mother in this film in a macro level represents the society on how it dictates what is good or bad, true or false, ugly and beautiful, right or wrong. Isabelle is the helpless people who are letting society mandate their character. Pwerta is guided by semiotics, psychoanalysis, gender and social constructivism. The film takes the form of a modified fairytale, combining the elements of drama, belief and construct."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Keywords: Gender expression; Constructivism (Philosophy).; Semiotics; Psychoanalysis